PERTUMBUHAN DAN PRODUKSI TIRAM (Pleurotus ostreatus) TERHADAP VARIASI JUMLAH BIBIT - Permadi, Muhammad Agung; Mukhlis, Mukhlis; Haldiman, Haldiman; Lubis, Rafiqah Amanda (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2021)
Mushrooms are organisms that do not have chlorophyll so that mushrooms cannot carry out photosynthesis. One type of mushroom that is commonly cultivated and consumed is the oyster mushroom (Pleurotus ostreatus). Oyster mushroom is a wood fungus that belongs to the Basidiomycetes class. Oyster mushrooms grow wild attached to weathered wood in the wild, by utilizing cellulose, hemicellulose and lignin as carbon sources to build cell mass. The purpose of this study was to study the growth and production of oysters (Pleurotus ostreatus) against variations in the number of seeds. This study used a completely randomized design (CRD) with six replications. The treatment in this study was the difference in the number of mushroom seeds planted in each baglog, namely 5, 8, 11 and 14 seeds. The data obtained were analyzed with variance and further tested with the DMRT test at the 5% level. Based on the research, it was found that the number of oyster mushroom seeds planted in baglog affects the growth of mycelium, the fresh weight of the first harvest and the harvesting age. The more oyster mushroom seeds planted in baglog, the wider the growth ofmycelium, the heavier the fresh weight of the first harvest and the faster the harvesting age.